First record of Tmesiphantes Simon, 1892 (Araneae, Theraphosidae) in Peru: a new species and its phylogenetic placement - NICOLETTA,MICAELA (2022)
Abstract The tarantula genus Tmesiphantes Simon, 1892 includes 20 valid species distributed in Argentina and Brazil. These spiders are distinguished from other Theraphosinae genera by the presence of an incrassate femur III, more evident in males, urticating hair types III and IV on the abdominal dorsum, few cuspules on the labium (0 to 30), maxillae with a maximum of 200 cuspules and sternum rounded. From recent examination of material from Peru, we discovered specimens that share all the morphological characters of Tmesiphantes, but did not fit with any known species. In the present study T. intiyaykuy sp. nov. is diagnosed, described, and illustrated. This new species resembles T. caymmii in the circular patch with stiff setae on midventral abdomen but can be distinguished by the shape of the palpal bulb and spermathecae. Also, we performed a phylogenetic analysis using morphological characters to infer the taxonomic placement of the new species. The analysis included 26 terminal species and 36 characters. Representatives of Tmesiphantes formed a monophyletic group and T. intiyaykuy sp. nov. is close related with T. caymmii. A dichotomous identification key and a geographic distribution map were constructed for recognized species of Tmesiphantes.